Direct push sensing in wetland (geo)archaeology: High-resolution reconstruction of buried canal structures (Fossa Carolina, Germany). (15th April 2018) - Hausmann, Jörg; Zielhofer, Christoph; Werther, Lukas; Berg-Hobohm, Stefanie; Dietrich, Peter; Heymann, Robert; Werban, Ulrike
Abstract: (Geo)archaeological trenching techniques in floodplain and wetland environments are challenging due to the impact of groundwater inflow and highly unstable trench edges. Alternatively, classical driving core techniques often correspond with the contraction of organic layers and bias in height accuracies. Here, we present the application of direct push sensing techniques for minimal-invasive (geo)archaeological surveys in zones affected by a high groundwater table, especially when high-resolution parameterization of buried (geo)archaeological structures is required. Two of these direct push applications are electrical conductivity logging and the measurement of colorimetric proxies in unconsolidated sediments. The tools provide multi-proxy information about layer structure, texture, and organic parameters. The high sensing speed allows recording a large data set with high vertical and lateral resolution. In this study we exemplary provide results of a buried canal structure within a valley in SW Germany. We present a high-resolution cross-section from a zone of high groundwater table. The canal is part of Charlemagne's summit canal ( Fossa Carolina ), an Early Medieval hydro-engineering project bridging the Central European Watershed. We compare the direct push sensing data with driving core samples and discuss prediction and generation options of parameter transfer from multiple one-dimensional logs to a two-dimensional canal cross-section of high-resolution. In this context, we use in situ -obtained colorimetric data and electrical conductivity as proxies for (geo)archaeological site characterization. We model organic fills of the canal by direct push logs and robust sediment data. Given the cost and time effectiveness of such tools, (geo)archaeological site information of high-depth accuracy was grown rapidly, compared to less densely performed drillings that require an additional high effort in laboratory analyses. The Carolingian excavation depth is 6 m below current surface. There is evidence for multiple organic layers in the trench fills, which reveal aquatic to semi-terrestrial stillwater deposition and, therefore, evidence of multiple Carolingian and post-Carolingian ponds. We have evidence for a conceptual width of the deep-buried artificial water course of at least 3–4 m. This allows a passage of Carolingian cargo scows with a payload of several tons in this central zone of the canal.